2018
DOI: 10.15446/ts.v20n1.71575
|View full text |Cite
|
Sign up to set email alerts
|

Trabajo Social e investigación: estrategias empoderadoras y de género en la universidad española

Abstract: ResumenEste artículo reflexiona sobre la función docente e investigadora del Trabajo Social y las consecuencias derivadas de la creciente jerarquización de los saberes, especialmente cuando las metodologías y epistemologías se relacionan con los estudios de las mujeres, de género y feministas en dicho campo de estudios. Basándonos en estrategias empoderadoras que algunas docentes hemos emprendido en España para superar las limitaciones del actual modelo de mercantilización científica, proponemos vincular el ám… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
0
0
2
Order By: Relevance
“…Regarding the first sociodemographic variable, gender, the proportion of women was observably higher than that of men (76.8% women versus 23.2% men), which is concordant with the typical gender ratio in the profession (Bañez Tello, 2005;Berasaluce Correa, 2009;Morales Villena, 2010;Roldán-García, Leyra-Fatou, & Contreras-Martínez, 2012;Green, 2015). This ratio indicates evolution in comparison with earlier studies, such as Palacios Gómez (2007), who found that women comprised more than 82% of social workers in 2000 and 80% in 2006.…”
Section: Methodological Notessupporting
confidence: 70%
See 1 more Smart Citation
“…Regarding the first sociodemographic variable, gender, the proportion of women was observably higher than that of men (76.8% women versus 23.2% men), which is concordant with the typical gender ratio in the profession (Bañez Tello, 2005;Berasaluce Correa, 2009;Morales Villena, 2010;Roldán-García, Leyra-Fatou, & Contreras-Martínez, 2012;Green, 2015). This ratio indicates evolution in comparison with earlier studies, such as Palacios Gómez (2007), who found that women comprised more than 82% of social workers in 2000 and 80% in 2006.…”
Section: Methodological Notessupporting
confidence: 70%
“…In a profession with a high degree of feminisation, as observed in numerous studies (Bañez Tello, 2005;Palacios Gómez, 2007;Berasaluce Correa, 2009;Morales Villena, 2010;Hall, 2011;Roldán-García, Leyra-Fatou, & Contreras-Martínez, 2012) and corroborated by our sample, it is interesting to analyse whether the valuation of the competencies has any difference as a function of the variable gender. Analysis using the  2 test (Pagano, 2011) finds that only competency 19.…”
Section: Gender Influencesupporting
confidence: 69%
“…Trabajo Social Global -Global Social Work, Vol 9, nº 17, julio-diciembre 2019, 65-88 La profesión propone enfoques metodológicos que articulan teoría y práctica, vincula a los profesionales y a las personas, genera alianzas entre academia y comunidad, dialécticas entre poderes globales y conocimientos locales, entre saberes trasnacionales y saberes situados (Morales y Agrela, 2018). En Trabajo Social se reflexiona lo epistemológico y lo empírico.…”
Section: La Dimensión Ambiental ¿Un áRea De Conocimiento O Un Dilema éTicopolítico En Trabajo Social?unclassified
“…Esto va en sintonía con los cambios que se empiezan a experimentar en la labor docente y el papel de la educación como temática de interés mundial (Nieva y Martínez, 2016). Este movimiento da lugar a la creación del Espacio Europeo de Educación Superior (EEES) que es consecuencia de la declaración de Bolonia (Morales y Agrela, 2018). El EEES se basa en un cambio de paradigma de aprendizaje, se pasa desde la enseñanza basada en el conocimiento hacía el aprendizaje de competencias (Fernández-Batanero, 2011).…”
Section: Introductionunclassified